Field parameters and biochemical soil properties from NEP 1, NEP 2, NEP 3, Nördlingen, southern Germany - Pejdanović, Snježana; Zvara, Ema; Marhan, Sven; Kandeler, Ellen; Poll, Christian; Oelmann, Yvonne; Neidhardt, Harald; Zielhofer, Christoph; Kühn, Peter (In: Zvara, Ema; Pejdanović, Snježana; Schneider, Birgit; Quante, Ella; Saeidi ghavi andam, Sara; Volosky, Diego; Lauer, Tobias; Fitzsimmons, Kathryn E; Marhan, Sven; Kandeler, Ellen; Poll, Christian; Oelmann, Yvonne; Neidhardt, Harald; Lindauer, Susanne; Friedrich, Ronny; Werther, Lukas; Frenzel, Peter; Kühn, Peter; Zielhofer, Christoph (2025): Multidisciplinary analyses of sediment-soil profiles from the Eger floodplain (Nördlingen, southern Germany) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.972856, 2025)
Soil physical-biogeochemical analyses were carried out on profiles NEP1, NEP2 and NEP3. Soil TC and TN were determined by CNS analysis, and total organic carbon (TOC) was determined by the difference between total inorganic carbon (TIC) and TC. Carbonate (CaCO₃) content was measured volumetrically using a Calcimeter and on air-dried, sieved (< 2 mm) and ground (ball mill) samples. The pH-values were measured on samples of profiles NEP1, NEP2, NEP3, which had less than 2% CaCO₃ content. Stable isotope ratios of δ¹³C and δ¹⁵N were analysed for the differentiation of C3 and C4 plants and the cultivation of legumes. The analyses were performed on air-dried, sieved (< 2mm) and ground (ball mill) samples. For ¹³C analysis, the soil samples were decarbonised with 10% HCl. In the field, separate samples were collected for the NEP1 and NEP2 profiles (28 samples in total) for analysis of urease activity and microbial biomass carbon (Cmic). Samples were stored at -18°C. Urease activity (enzyme analysis) is used to provide information on the input of urea and animal excrement. The mutual relationship between urease and Cmic was used to show and understand the past and present input of urea into the soil.
Keywords: CaCO₃; Eger floodplain; Eger River; floodplain deposits; microbial biomass carbon; Nördlingen; overbank silt-clay deposition; pH; Southern Germany; stable isotope ratios; TOC; urease activity